Unusual presentation of childhood Systemic Lupus Erythematosus - Agarwal Indira; Kumar Sathish (BMC, 2007)
Abstract Bullous systemic lupus erythematosus is a rare blistering condition with a distinctive combination of clinical, histological and immunopathologic features that together constitute a unique bullous disease phenotype. It is often associated with autoimmunity to type VII collagen. Here we report a child who presented with bullous systemic lupus erythematosus. Rapid resolution of the blisters occurred following treatment with dapsone.